BAGAS Efforts to Increase the Performance of Surakarta Polresta Police Crime Unit in the Settlement of Criminal Acts of Abuse to Increase Crime Clearance - Prasetyo, Bagas Umar (Advances in Police Science Research Journal, 2024)
Persecution is an expression either physically or verbally that reflects acts of aggression and attacks on a person's freedom or dignity that can be carried out by individuals or groups of people, Crime Clearance from abuse cases in the jurisdiction of the Surakarta Police is still relatively low. The police as state law enforcement officials have the duty and authority to resolve every crime that occurs in Indonesia, so research is being done to increase crime clearance for the crime of persecution in Surakarta. The theory used in this study consists of Management Theory, Competency Theory, and SWOT. Furthermore, there are concepts used in this study including the Effort Concept, the Performance Improvement Concept, the Criminal Investigation Concept, the Investigation Concept and the Crime Clearance concept. From research that has been carried out in the jurisdiction of the Surakarta Police, it shows that Crime Clearance from criminal acts of persecution is still low. This is because the implementation of the investigation is still not in accordance with the existing SOP, besides that it is also due to the lack of competence possessed by members of the Surakarta Police Criminal Investigation Unit Tipidum unit so that several efforts are made, which include carrying out the investigation SOP properly, increasing the ability of members with the Forum. Group Discussion and increase member motivation with a reward and punishment system. So that by solving this problem it is hoped that an outcome will be created in the form of increasing Crime Clearance for criminal acts of persecution in the legal area of ​​the Surakarta Police.